No evidence for association between late pregnancy maternal cortisol and gray matter volume in a healthy community sample of young adolescents - Tyborowska, Anna; Gruber, Katharina; Beijers, Roseriet; Kühn, Simone; Roelofs, Karin; de Weerth, Carolina (Frontiers in Neuroscience, 2022)
A compelling amount of animal and human research has shown that perceived maternal stress during pregnancy can affect the neurodevelopment of the offspring. Prenatal maternal cortisol is frequently proposed as the biological key mechanism underlying this link; however, literature that investigates the effects of prenatal cortisol on subsequent neurodevelopment in humans is scarce. By using longitudinal data from a relatively large community sample of mother-child dyads (N=73), this pre-registered study prospectively examined the role of maternal prenatal cortisol concentrations on subsequent individual differences in grey matter volume (GMV) and hippocampal subfield volumes at the onset of puberty of the offspring (12 years of age). Two markers of cortisol, that is evening cortisol and circadian decline over the day, were used as indicators of maternal physiological stress during the last trimester of pregnancy. Results indicate that prenatal maternal cortisol levels were not associated with GMV or hippocampal subfield volumes of the children. These findings suggest that late pregnancy maternal cortisol may not be related to the structural development of the offspring’s brain, at least not in healthy community samples and at the onset of puberty. When examining the influence of prenatal stress on offspring neurodevelopment, future investigations should delineate gestational timing effects of the cortisol exposure, cortisol assessment method, and impact of additional biomarkers, as these were not investigated in the current study.